Development of IBL Model with Scaffolding Technique to Improve Creative Thinking of Grade IV Students of SDN Kalisalam 2 - Lely Nur Fitria; Ludfi Arya Wardana; Didit Yulian Kasdriyanto (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
The low reasoning ability of students in processing information has an impact on learning outcomes and creative thinking skills. So it is necessary to develop a valid, practical, and effective learning model to improve students' creative thinking skills. The research method used was the Borg and Gall model which was modified into 8 stages. This research was tested on fourth grade students of SD Negeri Kalisalam 2. Data collection used questionnaires for student expert validators, and teachers, non-test assessments to measure students' creative thinking skills, and interviews. This research evaluates the validity, practicality, and effectiveness of the developed learning model. The results of expert validation showed that the model and learning materials were very valid with an average score of 90.16%. In detail, the learning model validator gave a score of 93.66%, while the material expert gave a score of 86.66%. The practicality assessment before and after the trial was 84% and 80% respectively, both in the “practical” category. The effectiveness of the model was measured through student questionnaires with an average of 79% (“effective”) and non-test assessment of creative thinking skills, where 16 out of 23 students showed improvement after the application of the learning model. This guidebook/prototype of inquiry-based learning model development with scaffolding techniques is considered effective for improving students' creative thinking skills, besides that this model can also help teachers in encouraging innovation in classroom learning to be more interesting.